2015
DOI: 10.1177/0047281615600637
|View full text |Cite
|
Sign up to set email alerts
|

Are We “There” Yet? The Treatment of Gender and Feminism in Technical, Business, and Workplace Writing Studies

Abstract: This article reexamines the treatment of gender and feminism in technical, business, and workplace writing studies—areas in which the three of us teach. Surprisingly, the published discourse of our field seems to implicitly minimize the gendered nature of business and technical writing workplaces and classrooms. To understand this apparent lack of focus, we review five technical and business communication academic journals and build on previous quantitative evaluations done by Isabelle Thompson in 1999 and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The overlap between care and multiculturalism exists in the care required to ensure program efforts are inclusive of multiple identities and cultural contexts. Teaching materials and methods affect the comfort and acceptance of women and diverse learners into vocational education settings (White et al, 2016). Attention to embedded influences on learning is necessary in traditionally male-dominated professions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlap between care and multiculturalism exists in the care required to ensure program efforts are inclusive of multiple identities and cultural contexts. Teaching materials and methods affect the comfort and acceptance of women and diverse learners into vocational education settings (White et al, 2016). Attention to embedded influences on learning is necessary in traditionally male-dominated professions.…”
Section: Resultsmentioning
confidence: 99%
“…Multiculturalism emphasizes the non-male and non-White learners who are often excluded from vocational education programs. Teaching materials and methods affect the comfort and acceptance of women and diverse learners into vocational education settings (White, Rumsey, & Amidon, 2016). In addition, instructors are often unprepared for classrooms that include diverse learners (hooks, 1994).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Leavy (2007) suggested that “many feminist researchers perform textual analysis from a deconstruction perspective in which a text is analyzed to see not only what is there but also what is missing, silenced, or absent” (p. 228). In an analysis of TPC textbooks and journals, White, Rumsey, and Amidon (2016) uncovered that these materials failed to interrogate dangerous and inaccurate perspectives of workplace neutrality, especially related to gender. They noted, “We were surprised and dismayed not at what we found in textbooks and professional journals, but what we didn’t find” (p. 29).…”
Section: Epistemology: Ways Of Knowing and Methods For Acknowledging mentioning
confidence: 99%
“…By contrast, disciplines that are business oriented or centered on the engineering sciences have historically had few to no courses focused on gender, race or sexuality (National Women's Studies Association NWSA, n.d.; Patton 2016). Administrators, faculty, and students, within these disciplines, are producing less knowledge about the interaction between hegemonic gender, race/ethnicity, and sexuality norms to sexual violence (Beddoes 2012;Mansfield et al 2014;White et al 2015).…”
Section: Gender Race/ethnicity and College Of Majormentioning
confidence: 99%